Functional Genomics in Pancreatic β Cells: Recent Advances in Gene Deletion and Genome Editing Technologies for Diabetes Research - Hu, Ming; Cherkaoui, Ines; Misra, Shivani; Rutter, Guy A. (Frontiers in Endocrinology, 2020)
The inheritance of variants that lead to coding changes in, or the mis-expression of, genes critical to pancreatic beta cell function can lead to alterations in insulin secretion and increase the risk of both type 1 and type 2 diabetes. Recently developed CRISPR/Cas9 gene editing tools provide a powerful means of understanding the impact of identified variants on cell function, growth and survival and might ultimately provide a means, most likely after the transplantation of genetically “corrected” cells, of treating the disease. Here, we review some of the disease-associated genes and variants whose roles have been probed up to now. Next, we survey recent exciting developments in CRISPR/Cas9 technology and their possible exploitation for β cell functional genomics. Finally, we will provide a perspective as to how CRISPR/Cas9 technology may find clinical application in patients with diabetes.